Factors Affecting the Resilience of Science and Engineering Students at GXUST in Liuzhou, Guangxi, China - Pang, Qianjing (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study examines the impact of four independent variables—self-efficacy, optimism, self-esteem, and physical exercise—on one dependent variable: resilience. The research aims to identify any statistically significant relationships among these variables. Research design, data and methodology: This study assessed validity using the Index of Item-Objective Congruence (IOC) and reliability through a pilot study with 30 participants (Cronbach's Alpha). A multiple linear regression analysis of 302 valid student responses from Guangxi University of Science and Technology examined relationships among variables. Additionally, a 12-week Intervention Design Implementation (IDI) program with 30 students was evaluated using a paired-sample t-test to compare pre- and post-intervention results. Results: Self-efficacy, optimism, self-esteem, and physical exercise significantly influenced resilience in the regression analysis. The paired-sample t-test showed significant improvements in all variables after the IDI program. Conclusions: This study confirms that self-efficacy, optimism, self-esteem, and physical exercise significantly enhance students' resilience, contributing to existing research on psychological resilience in higher education. The effectiveness of the Intervention Design Implementation (IDI) program highlights practical applications for developing targeted interventions to support student well-being. These findings can inform educational policies and mental health strategies aimed at fostering resilience. Future research should explore long-term effects and cross-cultural variations to enhance resilience-building approaches.